Riyadah Al - Nafs Menurut Al - Ghazali dan Aplikasinya dalam Kaunseling di PK MAINS - Mat Akhir, Noor Shakirah; Hanin Hamjah, Salasiah (Jurnal Usuluddin, 2007)
This article discussed al-Ghazalis riyadah al-nafs and its application in the counseling session conducted by counselors at PK MAINS (Pusat Kaunseling Majlis Agama Islam Negeri Sembilan). The discussion on al-Ghazalis riyadah al-nafs covers a few aspects such as faith (iman), devotional act (ibadah) and applying the mystical virtues (sifat al-mahmudah). The findings of this study showed that all aspects of al-Ghazalis riyadah al-nafs were discussed in the counseling session conducted by the counselor at PK MAINS.